2022
DOI: 10.1186/s13062-021-00314-6
|View full text |Cite
|
Sign up to set email alerts
|

LINC00885 promotes cervical cancer progression through sponging miR-3150b-3p and upregulating BAZ2A

Abstract: Background Cervical cancer (CC) is one of the most common malignancies affecting female worldwide. Long non-coding RNAs (lncRNAs) are increasingly indicated as crucial participants and promising therapeutic targets in human cancers. The main objective of this study was to explore the functions and mechanism of LINC00885 in CC. Methods RT-qPCR and western blot were used to detect RNA and protein levels. Functional and mechanism assays were respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…36 Current research has focused on breast and cervical cancers, but LINC00885 expression in OTSCC remains unclear. 37,38 Our findings revealed that LINC00885 is also upregulated in OTSCC. Therefore, the prognostic signature model based on the target gene of LINC00885 has high predictive efficacy in predicting the patient's prognosis after surgery or treatment.…”
Section: Discussionmentioning
confidence: 54%
“…36 Current research has focused on breast and cervical cancers, but LINC00885 expression in OTSCC remains unclear. 37,38 Our findings revealed that LINC00885 is also upregulated in OTSCC. Therefore, the prognostic signature model based on the target gene of LINC00885 has high predictive efficacy in predicting the patient's prognosis after surgery or treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have shown that overexpression of BAZ2A can predict tprostate cancer recurrence [ 65 ]. In addition, BAZ2A can have a regulatory role in hepatocellular carcinoma, cervical cancer, and chronic lymphoblastic leukemia [ 66 , 67 , 68 ]. MicroRNA (miRNA) is a noncoding RNA that pairs with target messenger RNA (mRNA) in a sequence-specific manner to regulate the expression of target genes [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA samples were treated with RNase-free DNase I (Qiagen), and RNA was quantified using a NanoDrop spectrophotometer (Thermo Scientific, Waltham, MA, USA). Total RNA was reverse-transcribed using Superscript III reverse transcriptase and oligo(dT) primer (Invitrogen) [ 78 , 79 ]. qRT-PCR was performed in ABI PRISM 7000 Sequence Detection System (Applied Biosystem, Waltham, MA, USA) with SYBR green ready mix (Applied Biosystem) and specific primers:…”
Section: Methodsmentioning
confidence: 99%